Communication conceptions in Hospital Nursing Management between head nurses in a University Hospital - Santos, José Luís Guedes dos; Prochnow, Adelina Giacomelli; Lima, Suzinara Beatriz Soares de; Leite, Joséte Luzia; Erdmann, Alacoque Lorenzini (Revista da Escola de Enfermagem da USP, 2011)
The objective of the following study was to analyze the conceptions that head nurses of a university hospital have about nursing communication management. It is a descriptive-exploratory study with an interpretative qualitative approach. The set of data was produced between September and October 2007 through interviews with 19 head nurses in a university hospital in Southern Brazil and submitted to thematic analysis. The nurses recognize the relevance of communication in nursing management, but have different perceptions: part of the research group understands communication from its interactive and dialogical perspective; others understand formal communication, based on the transmission and maintenance of standards and hospital routines, with emphasis on written communication. Further discussion about the triad communication, management and dialogue is required in order to build more interactive forms of hospital nursing care management.